2018
DOI: 10.3390/genes9060276
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus Paracasei Expressing a Nucleic Acid-Hydrolyzing Minibody (3D8 Scfv) Enhances Probiotic Activities in Mice Intestine as Revealed by Metagenomic Analyses

Abstract: Probiotics are well known for their beneficial effects for animals, including humans and livestock. Here, we tested the probiotic activity of Lactobacillus paracasei expressing 3D8 scFv, a nucleic acid-hydrolyzing mini-antibody, in mice intestine. A total of 18 fecal samples derived from three different conditions at two different time points were subjected to high-throughput 16S ribosomal RNA (rRNA) metagenomic analyses. Bioinformatic analyses identified an average of 290 operational taxonomic units. After ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…Similarly, Cho et al. (2018) reported that Firmicutes and Proteobacteria provide the greatest contributions to the bacterial taxonomic composition of the fecal microbiota of the L. salivarius ‐treated group at the phylum level. Microbial balance can be stimulated with strains of the genus Lactobacillus , which acts as a dominant genus in the small intestine of chickens (Barnes, Mead, Barnuml, & Harry, 1972; Lu et al., 2003).…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Cho et al. (2018) reported that Firmicutes and Proteobacteria provide the greatest contributions to the bacterial taxonomic composition of the fecal microbiota of the L. salivarius ‐treated group at the phylum level. Microbial balance can be stimulated with strains of the genus Lactobacillus , which acts as a dominant genus in the small intestine of chickens (Barnes, Mead, Barnuml, & Harry, 1972; Lu et al., 2003).…”
Section: Discussionmentioning
confidence: 85%
“…71 Lead (Pb) treatment has been shown to reduce the proportion of Helicobacters in mice while chlorogenic acid was shown to have a remarkable reversion effect on the gut microbiota composition, the change being induced by Pb. 74 Long-term intake of ginseng extracts facilitates the growth of probiotics in the gut microbiota of rats and inhibits the colonization of some pathogenic bacteria including Helicobacter. 73 Lactobacillus paracasei, expressing a nucleic acidhydrolyzing mini-antibody (3D8 scFv) protein, was shown to enhance probiotic activity in the mouse intestine and to decrease the population of harmful bacteria such as Helicobacter species.…”
Section: G Row Th and Survival Of Non -Helicobac Ter Pylori Heli Comentioning
confidence: 99%
“…73 Lactobacillus paracasei, expressing a nucleic acidhydrolyzing mini-antibody (3D8 scFv) protein, was shown to enhance probiotic activity in the mouse intestine and to decrease the population of harmful bacteria such as Helicobacter species. 74 Long-term intake of ginseng extracts facilitates the growth of probiotics in the gut microbiota of rats and inhibits the colonization of some pathogenic bacteria including Helicobacter. 75 A decoction of Codonopsis pilosula Nannf (also known poor man's ginseng) was shown to alleviate gut microbial dysbiosis in a dextran sulfate sodium-induced colitis in mice by simultaneously stimulating the growth of probiotics and inhibiting the growth of pathogenic bacteria, including Desulfovibrio, Alistipes, and Helicobacter.…”
Section: G Row Th and Survival Of Non -Helicobac Ter Pylori Heli Comentioning
confidence: 99%
“…As revealed by our previous research, Lactobacillus casei ATCC 334 expressing 3D8 scFv (a nucleic acid-hydrolyzing antibody) exerted an antiviral effect on murine norovirus ( 2 ). It also showed enhanced probiotic activity in the intestines of mice by increasing the population of Pediococcus acidilactici , another probiotic ( 3 ). Previous studies have thus confirmed that lactic acid bacteria expressing 3D8 scFv could serve as an antiviral drug.…”
Section: Announcementmentioning
confidence: 99%